Chili pepper preference development and its impact on dietary intake: A narrative review - Siebert, Emily; Lee, Soo-Yeun; Prescott, Melissa Pflugh (Frontiers in Nutrition, 2022)
A preference for chili pepper can be an acquired taste. The contrast between a chili lover and a hater illustrates the complexities involved in forming an appreciation for food that evokes a fiery pain sensation. This narrative review aims to understand the factors behind chili pepper preference formation across the life course and how individual chili pepper preferences can impact eating behaviors and dietary intake. This review was conducted using three databases, yielding 35 included articles. Results suggest five determinants of chili pepper preferences: culture, exposure, gender, genetics, and personality. Collective findings indicate that the strongest influences on preference acquisition include the individual environment from childhood to adulthood and repeated exposure to spicy flavors. With frequent exposure to spicy food, the perceived burn becomes less intense. Culture also influences exposure to chili peppers, with the highest consumption patterns seen within Mexico and some Asia countries. Additionally, males reported having a stronger preference for spicy foods than females. Twin studies illustrated that genetics influenced spicy taste preferences, underscoring the complexity of developing individual taste preferences. As for the impact of capsaicin-containing food on individual eating behaviors and dietary behaviors, appetite effects depend on the dose of capsaicin consumed, but three studies found a change in sensory desires for sweet and fatty foods after finishing a capsaicin-containing dish. Inconsistent results were reported for chili pepper’s effects on hunger and satiety after consumption, but changes in specific food desires were observed. The impact of chili pepper on appetite and calories consumed was inconsistent, but the greater amount of capsaicin ingested, the greater the effect. Capsaicin’s potential to be used for weight control needs to be further reviewed. In conclusion, evidence suggests that chili pepper preferences may be linked to innate and environmental aspects such as an individual’s culture, gender, and genetics. Extrinsic factors like repeated exposure may increase the liking for spicy foods.